Antenatal Care Utilization during Covid-19 Pandemic among Pregnant Women in Tangerang City Indonesia - Pratiwi, Kartika Yuni; Ariyanti, Fajar; Baequni, Baequni; Nasir, Narila Mutia (Journal of Health Education, 2022)
Background: The COVID-19 Pandemic has affected access, quality, and Maternal and Child Health (MCH) services coverage. This study aimed to analyze the factors associated with antenatal care service utilization among pregnant women in Tangerang City.Methods: This was a cross-sectional study using the accidental sampling method. We recruited 171 pregnant women as respondents. Data were collected using a questionnaire and distributed via Google Forms. We performed univariate and bivariate analyses (Chi-Square with 95% CI).Results: The study showed that the fear of COVID-19 (p-value = 0.050) and the availability of services (p-value = 0.047) were factors related to the utilization of antenatal care services.Conclusion: The study concluded that only 61.4% of respondents had utilized antenatal care services during the COVID-19 pandemic. It is expected that health workers will continue to provide education as well as information through health promotion regarding pregnancy check-ups during the COVID-19 Pandemic to pregnant women.